PENGARUH KETELADANAN GURU TERHADAP KEDISIPLINAN SISWA MTs Al-FATHONIYAH KOTA SERANG - Iis Faridah; Sukhoiri, Sukhoiri (Journal of Innovation Research and Knowledge, 2023)
The research objectives is find out the effect of the teacher's example on student discipline. This type of research is descriptive research, with data collection techniques of observation, interviews, questionnaires, documentation, and literature study. This research was conducted at MTs Al-Fathoniyah at Serang. The results of the research show that the correlation coefficient data (r????????) = 0.85 is between 0.80-100 whose interpretation is the influence of the teacher's example (variable X) on student discipline (variable Y) there is a strong or high correlation. Furthermore, data processing based on the results of the significance test is known, tℎ???????????????????? = 17.327 > from t???????????????????? = 2.021, the interpretation of which is that there is a significant influence between the teacher's example on student discipline. The contribution of variable X to variable Y using the coefficient of determination (CD) is 72.25% while the remaining 27.75% is influenced by other factors.